Not All Acne Is Acne Vulgaris - Gollnick, Harald P (Deutscher Arzte Verlag, 2014)
BACKGROUND: Acne is the most common skin disease in adolescence, with a prevalence of nearly 100%. About 60% of affected adolescents have mild acne for which they use non-prescription preparations without consulting a physician. The remaining 40% constitute the population of acne patients seen in medical practice. The course of acne can be either acute or chronic; its manifestations can appear in waves, sometimes with dramatically severe inflammation leading rapidly to scarring. Acne often has adverse emotional consequences. Its treatment is markedly better than in the past because of new pharmacological and physicochemical approaches and because evidence-based guidelines are now available. METHODS: This article is based on a selective review of the literature and also incorporates the authors’ own clinical and scientific experience. RESULTS: Acne vulgaris of grade I or II in an adolescent is generally not hard to treat. In contrast, the more severe grades III and IV and conglobate acne often present a therapeutic challenge, as they are associated with varying constellations of acute lesions, scarring, inflammation, and emotional disturbances. These conditions often require systemic treatment with tetracyclines, which are especially useful because of their para-antibiotic anti-inflammatory effect. Severe cases must be treated with isotretinoin. Women can benefit from anti-androgenic contraceptive drugs. Retinoids or azelaic acid are used in maintenance therapy to suppress the formation of microcomedones, the precursor stage of acne lesions. CONCLUSION: A variety of effective treatments for acne are available, depending on the severity of the condition.